Cerebrospinal Fluid Drop Metastases of Canine Glioma: Magnetic Resonance Imaging Classification - Bentley, R. Timothy; Yanke, Amy B.; Miller, Margaret A.; Heng, Hock Gan; Cohen-Gadol, Aaron; Rossmeisl, John H. (Frontiers in Veterinary Science, 2021)
Dissemination of glioma in humans can occur as leptomeningeal nodules, diffuse leptomeningeal lesions, or ependymal lesions. Cerebrospinal fluid (CSF) drop metastasis of glioma is not well-recognized in dogs. Ten dogs with at least two anatomically distinct and histologically confirmed foci of glioma were included in this study. The 10 dogs underwent 28 magnetic resonance imaging (MRI) examinations, with distant CSF drop metastasis revealed in 13 MRIs. The CSF drop metastases appeared as leptomeningeal nodules in four dogs, diffuse leptomeningeal lesions in six dogs, and ependymal lesions in seven dogs; six dogs had a combination of lesion types. Primary tumors were generally T2-heterogeneous and contrast-enhancing. Many metastases were T2-homogeneous and non-enhancing. Diffuse leptomeningeal lesions were seen as widespread extra-axial contrast-enhancement, again very dissimilar to the intra-axial primary mass. Primary masses were rostrotentorial, whereas metastases generally occurred in the direction of CSF flow, in ventricles, CSF cisterns, and the central canal or leptomeninges of the cervical or thoracolumbar spinal cord. Seven of the dogs had received therapy limited to the primary mass, such as surgery or stereotactic radiation, then developed metastasis in the following months. CSF drop metastasis of glioma may take a very different appearance on MRI to the primary mass, including periventricular lesions that are more homogeneous and less contrast-enhancing, rostral horn signal changes, or leptomeningeal enhancement ventral to the brainstem or encircling the spinal cord.